2020
DOI: 10.1002/mdc3.13122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non‐Motor Symptoms and Non‐Motor Fluctuations in Parkinson's Disease Using the MDS‐NMS

Abstract: Background Non‐motor symptoms (NMS) are frequent in Parkinson's disease (PD). Objectives To estimate the prevalence of NMS and of non‐motor fluctuations (NMF) using the Movement Disorders Society‐Non‐Motor Rating Scale (MDS‐NMS) and other scales assessing NMS, and their relationship with sex and PD severity. Methods Cross‐sectional study with a sample of 402 PD patients. The Hoehn and Yahr staging system (HY), Clinical Impression of Severity Index for PD (CISI‐PD), MDS‐NMS (including NMF‐ subscale), Non‐Motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 50 publications
5
35
0
Order By: Relevance
“…Importantly, we observed that mood improvement 6 months after starting with safinamide correlated with health-related QoL improvement. Systematic reviews of depression in epidemiologic PD studies describe a combined prevalence about 35% [ 23 ], although some publications report frequencies over 50% [ 13 , 24 ]. This prevalence may be higher in patients with disease later stages [ 22 , 25 27 ] or women [ 12 , 26 ], although depression‐type frequency or BDI-II score does not seem to change with disease duration [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, we observed that mood improvement 6 months after starting with safinamide correlated with health-related QoL improvement. Systematic reviews of depression in epidemiologic PD studies describe a combined prevalence about 35% [ 23 ], although some publications report frequencies over 50% [ 13 , 24 ]. This prevalence may be higher in patients with disease later stages [ 22 , 25 27 ] or women [ 12 , 26 ], although depression‐type frequency or BDI-II score does not seem to change with disease duration [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly subjects with executive dysfunction have a poorer response to serotonin-reuptake-inhibiting antidepressants [ 30 ]. Anxiety is even more frequent than depression in PD [ 24 ], and its presence is a predictor of worse response to antidepressants [ 31 ]. In a meta-analyses conducted by Huang et al [ 32 ], MAOB-I significantly reduced depressive symptoms, but in the subgroup analysis this decrease was significant only in patients with early PD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, lower education levels also characterized PD-MCI [35]. About 10% of PD patients develop dementia every year, which is four to six times higher than that of non-PD patients [36], and the life-long prevalence of PDD is almost 80% [25,28,37,38]. Patients with PD-MCI are also more likely to eventually develop dementia [25] and to develop it earlier [39,40] than PD patients without cognitive impairment.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…It is characterised by bradykinesia, rigidity and tremor, and these motor symptoms are related to dopamine depletion caused by a progressive loss of dopaminergic neurones [2]. PD is further associated with a broad spectrum of non-motor symptoms, experienced by most patients, such as cognitive deficits, loss of smell, and depression [3,4]. Alpha-synuclein (α-Syn) has been implicated in regulating synaptic vesicle mobilization and soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex assembly and its regulatory actions are necessary to maintain homeostasis at synapses during intense activity, especially in dopaminergic neurons (reviewed in [5,6]).…”
Section: Introductionmentioning
confidence: 99%